Li-doped C20 nanocage and its derivatives for gas sensing application: A density functional theory study - Poonam Parkar; Mohsen Doust Mohammadi; Ajay Chaudhari (Talanta Open)
We studied the gas-sensing properties of Li-decorated C20 nanocage and its derivatives, presenting these materials as novel candidates for sensing applications. The derivatives of C20 considered are either B-substituted, N-substituted or B and N co-substituted C20 Nanocages. Toxic gases H2S and NH3, were selected for evaluation. Out of 15 derivatives analysed, 10 were confirmed to be stable for Li-doping and gas sensing application. The C12N8 nanocage demonstrating the strongest Li-anchoring, characterized by a high Li-binding energy of 3.81 eV. The Li-decoration introduced spin polarization near the Fermi level, reflected in asymmetric spin-up and spin-down states, which indicated the magnetic nature of the resulting complexes. Substantial changes in the electronic structure of the nanocages upon interaction with H2S and NH3 molecules are observed, both of which were found to adsorb favourably over a broad temperature and pressure range. H2S molecule was observed to undergo physisorption, while NH3 exhibited strong chemisorption across all the nanocages. Recovery time analysis highlighted that all nanocages displayed practical recovery times for H2S, with the C10B10 nanocage showing the shortest recovery time, emphasizing its potential as a highly efficient sensor for H2S detection. The designed nanocages show better gas sensing performance for H2S gas molecule than NH3.